Structural and Photoluminescence Properties of ZnO Thin Films Deposited by Ultrasonic Spray Pyrolysis - Sugihartono, Iwan; Handoko, Erfan; Fauzia, Vivi; Arkundato, Artoto; Sari, Lara Permata (UI Scholars Hub, 2018)
Zinc oxide (ZnO) thin films on a silicon (Si) (111) substrate were grown herein using ultrasonic spray pyrolysis at 450 °C with different Zn concentrations. The ZnO thin films had X-ray diffraction patterns of a polycrystalline hexagonal wurtzite structure. The (002) and (101) peak intensities changed under different Zn concentrations. Furthermore, according to Scherer's and Stokes–Wilson equations, the crystallite size and the internal strain of the ZnO thin films in the (002) and (101) peaks changed with the Zn concentration. Optically, the photoluminescence spectra indicated that the ratio of the UV/GB emission of the ZnO thin films was the highest at the Zn concentration of 0.02 mol/mL. We predicted that by increasing the Zn concentrations, the nonradiative transitions, which originated from defects, such as lattice and surface defect, become dominant. In conclusion, the ZnO thin films with the Zn concentration of 0.02 mol/mL had a better crystalline and optical quality.